Evaluation evidence in RBC: School Feeding - Molinas, Luca (2018)
The IFPRI-Egypt Seminar Series is part of the United States Agency for International Development (USAID) funded project called “Evaluating Impact and Building Capacity” (EIBC) that is implemented by IFPRI. The seminar supports USAID’s Agribusiness for Rural Development and Increasing Incomes (ARDII) project’s objectives. This seminar was held in partnership with WFP under the title of "Utilizing evidence-based research to inform policy: The Case of School Feeding Programs"